Image Decomposition Using Wavelet Transform (International Journal of Engineering and Computer Science, 2013)
In this work, image has been decomposed on wavelet decomposition technique using different wavelet transforms with different levels of decomposition. Two different images were taken and on these images wavelet decomposition technique is implemented. The parameters of the image were calculated with respect to the original image. Peak signal to noise ratio (PSNR) and mean square error (MSE) of the decomposed images were calculated. PSNR is used to measure the difference between two images. From the several types of wavelet transforms, Daubechie (db) wavelet transforms were used to analyze the results. The value of threshold is rescaled for denoising purposes. De-noising methods based on wavelet decomposition is one of the most significant applications of wavelets